Doing research in a postcolonial context. Navigating the unconditional from a biographical research perspective - Pilch Ortega, Angela (Adult Education Discourses, 2025)
The aim of the article is to focus on the question of what is absolutely necessary for me in research and how to navigate it. To answer this question, I will refer to key experiences that are of great importance to me as a researcher. Based on my previous research, particularly in relation to my investigations in the highlands of Chiapas in Mexico, I will attempt to identify key elements that are essential to my research. More specifically, I will address important challenges that have fundamentally questioned and influenced my understanding of research and have been important for my development as a scientist. In particular my research in postcolonial contexts has led me to many limits of my understanding of science and helped me to explore new paths and to further develop my original attitude as a researcher. Thinking about the question of the legitimacy of scientific (re-)presentation, for example, was an important turning point for my understanding of research. Against this backdrop I will focus on doing research with postcolonial narratives and will highlight related epistemological, methodological and ethical issues I had to deal with during my research.